Relationship between Sociodemographic Factors and Mother - Wardani, Endah Kusuma; Hastuti, Uki Retno Budi; Adriani, Rita Benya (Journal of Maternal and Child Health, 2017)
Background: Exclusive breastfeeding for 6 months is every baby